Characterization of chitinases of polycentric anaerobic rumen fungi - Novotná, Zuzana; Fliegerová, Kateřina; Šimůnek, Jiří (Folia microbiologica, 2008)
Chitinolytic systems of anaerobic polycentric rumen fungi of genera Orpinomyces and Anaeromyces were investigated in three crude enzyme fractions - extracellular, cytosolic and cell-wall. Endochitinase was found as a dominant enzyme with highest activity in the cytosolic fraction. Endochitinases of both genera were stable at pH 4.5-7.0 with optimum at 6.5. The Orpinomyces endochitinase was stable up to 50 degrees C with an optimum for enzyme activity at 50 degrees C; similarly, Anaeromyces endochitinase was stable up to 40 degrees C with optimum at 40 degrees C. The most suitable substrate for both endochitinases was fungal cell-wall chitin. Enzyme activities were inhibited by Hg(2+) and Mn(2+), and activated by Mg(2+) and Fe(3+). Both endochitinases were inhibited by 10 mmol/L SDS and activated by iodoacetamide.
Keywords: teplota; stabilita enzymů; Enzyme Stability; Chitin; Rumen; zvířata; chitinasy; bachor; Neocallimastigales; Anaerobiosis; Chytridiomycota; koncentrace vodíkových iontů; Fungal Proteins; anaerobióza; Chitinases; chitin; Animals; fungální proteiny; Hydrogen-Ion Concentration; Temperature